An Investigation into Social Learning Activities by Practitioners in Open Educational Practices - Schreurs, Bieke; Van den Beemt, Antoine; Prinsen, Fleur; Witthaus, Gabi; Conole, Gráinne; De Laat, Maarten (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
By investigating how educational practitioners participate in activities around open educational practices (OEP), this paper aims at contributing to an understanding of open practices and how these practitioners learn to use OEP. Our research is guided by the following hypothesis: Different social configurations support a variety of social learning activities. The social configuration of OEPs is investigated by an operationalization into the dimensions (1) practice, (2) domain, (3) collective identity, and (4) organization. The results show how practitioners of six different OEPs learn, while acting and collaborating through a combination of offline and online networks. The findings of our study lead to practical implications on how to support participation in OEP, and thereby stimulate learning in (online) networks of OEP.